2018
DOI: 10.1002/jcb.27623
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation expression of toll‐like receptor4 (TLR4) caused by the dysregulation of microRNA‐140‐5p is responsible for the development of postoperation infection

Abstract: Background: Toll-like receptor4 (TLR4) has proven to be an important factor that's responsible for the development of postoperation infection. MicroRNAs (miRNAs) are widely regarded as key mediators of gene expression. The objectives of our study were to identify miRNA(s) and the target genes differentially expressed in monocytes in the individuals with postoperation infection.Methods: MiRNA microarrays were performed to identify and compare miRNA expression in monocytes from those with or without postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…These observations are in agreement with elevated inflammatory markers, particularly IL‐6 levels, in SM‐exposed animals 33,34 . Interestingly, recent studies showed the regulation of IL‐6 and other inflammatory genes by miR‐140, 24,25,35 which further strengthens our observations, underscoring the role of miR‐140 in CEES‐induced injury.…”
Section: Discussionsupporting
confidence: 91%
“…These observations are in agreement with elevated inflammatory markers, particularly IL‐6 levels, in SM‐exposed animals 33,34 . Interestingly, recent studies showed the regulation of IL‐6 and other inflammatory genes by miR‐140, 24,25,35 which further strengthens our observations, underscoring the role of miR‐140 in CEES‐induced injury.…”
Section: Discussionsupporting
confidence: 91%